Adoption of the Declaration of State Sovereignty of the Soviet Republic of Tuva (extract from the manuscript "Lessons of life and a quest”) - Ondar, Chimit-Dorzhu B. (The New Research of Tuva, 2012)
A well-known public politician of Tuva shares his memoirs about the Tuvan politics during the period of "Parade of sovereignties” in 1990, tells the story of adoption of Declaration of State Sovereignty, one of the authors of which he was.
Keywords: Tuva; politics; 1990’s; memoirs; sovereignty; Declaration; deputies; Supreme Soviet